Pertanggungjawaban Pidana Affiliator Binery Option Studi Kasus Platform Investasi Binomo: - - Nita Anisatul Azizah (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
Technological advances are marked by the rise of electronic users , sometimes these technological developments can be a terrible scourge for humans if user not good at using technology that . The extent of the reach found on the internet has an impact on the birth of new types of crime where we know that criminals do not see the place and time of committing a crime. Recently, Indonesia was shocked by the presence of new crime in the world of economics. The crime in question is binary options or can we say binary options . Type the method used in the research this is is a qualitative research in the implication of this method is descriptive analytical. The approach used by researchers in solving existing problems is juridical – normative. Result this research show Binary option transactions on Binomo investments are included in the crime of gambling because they have fulfilled the elements of a criminal act as stated in Article 303 Paragraph (3) of the Criminal Code, namely the possibility of getting a profit which only depends on the luck of the estimate made by the investor, if possible. If the estimate is correct then the investor will get the profit, on the other hand, if not the money that was wagered at the beginning of the transaction will be forfeited instantly, this is the same with gambling activities. Affiliates who are in charge of promoting Binomo to the public can be subject to criminal penalties, in addition to the legal status of the platform is not registered , what is the reason that the affiliate's actions in carrying out their activities violate Article 378 of the Criminal Code in conjunction with Article 28 Paragraph (1) of the ITE Law and or Articles 3, 5 and 10 of Law Number 8 of 2010 concerning Prevention Eradication of money laundering offences.